2018
DOI: 10.1038/s41467-018-02925-6
|View full text |Cite
|
Sign up to set email alerts
|

In-situ liquid cell transmission electron microscopy investigation on oriented attachment of gold nanoparticles

Abstract: Inside a liquid solution, oriented attachment (OA) is now recognized to be as important a pathway to crystal growth as other, more conventional growth mechanisms. However, the driving force that controls the occurrence of OA is still poorly understood. Here, using in-situ liquid cell transmission electron microscopy, we demonstrate the ligand-controlled OA of citrate-stabilized gold nanoparticles at atomic resolution. Our data reveal that particle pairs rotate randomly at a separation distance greater than twi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
224
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(230 citation statements)
references
References 52 publications
6
224
0
Order By: Relevance
“…The both of above two works revealed the interaction of nanoparticles during the growth process which are significant to understand the growth kinetics during the formation of single metal electrocatalysts. Except for Pt, the oriented attachment also existed during the formation process of other metals like Au, which confirmed the generality of this behavior in the formation of metal nanoparticles. It has been demonstrated that the coalescence and attachments could lead to the formation of nanoparticle and nanowires, which generally depends on the diffusion of the atoms: fast diffusion is in favor of nanoparticles; or insufficient diffusion tends to nanowires.…”
Section: Zero‐dimensional Nanoparticles Formationsupporting
confidence: 60%
“…The both of above two works revealed the interaction of nanoparticles during the growth process which are significant to understand the growth kinetics during the formation of single metal electrocatalysts. Except for Pt, the oriented attachment also existed during the formation process of other metals like Au, which confirmed the generality of this behavior in the formation of metal nanoparticles. It has been demonstrated that the coalescence and attachments could lead to the formation of nanoparticle and nanowires, which generally depends on the diffusion of the atoms: fast diffusion is in favor of nanoparticles; or insufficient diffusion tends to nanowires.…”
Section: Zero‐dimensional Nanoparticles Formationsupporting
confidence: 60%
“…Those events include quantum tunneling, charge transfer, chemical interfacial damping, and surface dipole formation. In the view of recent quantum‐tunneling studies in the nanoparticle gap less than 1 nm, for example, the presence of adatoms or altered molecular orientation on the surface of gold nanoparticles may cause an error in the estimated distance of nanoparticle gap up to 0.5 nm compared to a simplified surface model . A precise description on nanoparticle surfaces will provide plausible explanations of puzzling experimental observations.…”
Section: Introductionmentioning
confidence: 99%
“…To load pocket and crease cells, a droplet of 10 × 10 −3 m solution of HAuCl 4 was placed on the TEM grid prior to transfer of the graphene top layer by the LAT method. The formation of Au nanoparticles from HAuCl 4 solution was chosen as a test reaction because it is a well‐documented procedure that has been extensively characterized in literature . After 10 s of beam exposure, nanoparticles of varying sizes had formed in all liquid cells, with high contrast regions being, indeed, pockets of encapsulated liquid ( Figure a–c).…”
Section: Resultsmentioning
confidence: 99%